Analyzing The Impact Of Artificial Intelligence (AI) On The Future Of English Language Teaching And Learning - Dina Amaliyah Mushthoza; Nur Syariatin; Olivia Tahalele; Sandra Ivonnie Telussa; Rasmita Rasmita; Sabil Mokodenseho (Journal on Education, 2023)
This literature review examines the impact of artificial intelligence (AI) on the future of English language teaching and learning. The rapid advancement of AI technologies has brought significant changes to various fields, including education. In the context of English language education, AI has been integrated into teaching and assessment practices to enhance learning outcomes and instructional experiences. This review explores the effectiveness of AI tools, such as intelligent tutoring systems and chatbots, in improving language proficiency and learner engagement. It also examines AI-driven language assessment methods, including automated scoring systems and speech recognition technology. The pedagogical implications, challenges, and ethical considerations associated with the integration of AI in language education are discussed. The role of teachers in AI-driven classrooms and the potential for learner autonomy are highlighted. Future directions for research and the need to address the impact of AI on learners from diverse backgrounds are identified. The findings underscore the potential benefits of AI in English language teaching and learning, while emphasizing the importance of responsible implementation and ongoing evaluation to ensure ethical and equitable practices.